Are contemporary antifungal doses sufficient for critically ill patients? Outcomes from an international, multicenter pharmacokinetics study for screening antifungal exposure in intensive care units— the SAFE‑ICU study - Roberts, Jason A.; Sime, Fekade B.; Lipman, Jeffrey; Hernandez‑Mitre, Maria Patricia; Baptista, Joao Pedro; Bruggemann, Roger J.; Darvall, Jai; Waele, Jan J. De; Dimopoulos, George; Lefran, Jean‑Yves; Mat Nor, Mohd Basri; Rello, Jordi; et al. (Springer Nature, 2025)
Purpose Appropriate antifungal therapy is a major determinant of survival in critically ill patients with invasive fungal disease. We sought to describe whether contemporary dosing of antifungals achieves therapeutic exposures in critically ill patients.